It’s possible to measure racism! Analysis of measures and scales of the racism construct - Marcelino, Karina Francine; Moraes, Mário César Barreto (Revista de Administração da UFSM, 2024)
Purpose: This research aims to analyze the construction and validation of measures and scales of the racism construct through a systematic literature review. The purpose is to examine how these instruments are built based on statistical recommendations for scale development. Methodology: A systematic literature review followed well-defined inclusion and exclusion criteria. Data were collected from databases available on the Portal de Periódicos Capes, covering a period up to December 2023 (with no start date limitation). After removing duplicate articles and applying the defined filters, six studies were selected for the analysis of scale construction. Findings: Three specific scales were identified to measure and evaluate the racism construct: the Modern Racism Scale, the Symbolic Racism Scale, and the Ethno-Racial Attitudes Scale. Although there is a predominance of studies on the Modern Racism Scale, other instruments were excluded from the analysis corpus due to non-compliance with inclusion criteria, especially related to article availability. Originality: Among the 82 analyzed articles, those focused on measures and scales of the racism construct do not provide an analysis of the development of these instruments. This study brings to light an analysis of the construction and validation of these measures and scales.